Assessment of cassava mosaic disease (CMD) intensity and whitefly (Bemisia tabaci) population in Cameroon based on field surveys - Bahoya, Joseph Aime Lauryn; Levai , Lewis Dopgima; Fogang, Patrick Kenfack; Monono , Ekwa Yawa; Neba , Desmond Ngwa; Tiendrébéogo, Fidèle; Tchoumbougnang , François; Niemenak , Nicolas; Obiageli , Angela Eni; Pita , Justin Simon; Doungous, Oumar (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Cassava mosaic disease (CMD) remains a major constraint to cassava (Manihot esculenta Crantz) production in Cameroon. This study aimed to generate updated epidemiological data on CMD across the country. Surveys were conducted in 342 fields across the ten administrative regions of Cameroon between January and September 2022, following a standardized protocol adopted by all fourteen countries participating in the Central and West African Virus Epidemiology for Food Security (WAVE) program. In each field, 30 plants were assessed for CMD incidence, severity, whitefly population, and mode of infection. CMD symptoms were observed in all ten regions. The overall mean CMD incidence was 54.72%, with a mean severity score of 2.39. Incidence, severity, and whitefly populations varied significantly among regions. The South Region recorded the highest mean incidence (74.34%), while the Far North had the lowest (18.97%). The Adamawa Region exhibited the highest mean severity (2.63), whereas the South West Region had the lowest (2.19). Whitefly abundance per plant was greatest in the South West (21.44) and lowest in the Far North (0.40). PCR amplification and sequencing confirmed the presence of cassava mosaic geminiviruses (CMGs) in leaf samples. A positive correlation was detected between mean whitefly abundance and CMD incidence, while altitude was negatively correlated with whitefly numbers. Both CMD incidence and whitefly populations were higher in intercropped fields than in monocropped fields. Notably, intercropping cassava with maize reduced whitefly populations, while intercropping with sweet potato lowered CMD incidence. The primary source of CMD infection was the use of infected cuttings. These findings provide valuable insights for the development of targeted interventions and improved management strategies for CMD in Cameroon.